2018
DOI: 10.1007/s11368-018-2158-1
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved humic substances supplied as potential enhancers of Cu, Cd, and Pb adsorption by two different mangrove sediments

Abstract: Purpose The external supply of humic substances has been recently suggested for the remediation of metal-polluted sediments; however, little is known about how to supply them and their effects on metal mobility. The study sought to investigate the sediment-metals-humic substance interaction in mangrove forest sediments. We aimed to evaluate the sediment adsorption potential in the case of large and rapid metal loads, as recently occurred in the Doce River (Brazil). Materials and methods In each mangrove forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…HSs can also influence the fate of toxic substances by regulating their transport and stabilization in soil and, consequently, their effect on plants and soil-populating bacteria [ 78 ]. Pittarello et al [ 93 ] exploited this behavior towards mangrove sediments and found that the sediments’ absorbing capacity of copper (Cu), cadmium (Cd), and lead (Pb) was significantly increased by the addition of HSs. In another study, the same authors tested the effect of different dosages of HS PBs in mangrove ( Avicennia germinans ) seedlings grown in Cd-contaminated solutions [ 94 ].…”
Section: Pbs For Phytoremediationmentioning
confidence: 99%
“…HSs can also influence the fate of toxic substances by regulating their transport and stabilization in soil and, consequently, their effect on plants and soil-populating bacteria [ 78 ]. Pittarello et al [ 93 ] exploited this behavior towards mangrove sediments and found that the sediments’ absorbing capacity of copper (Cu), cadmium (Cd), and lead (Pb) was significantly increased by the addition of HSs. In another study, the same authors tested the effect of different dosages of HS PBs in mangrove ( Avicennia germinans ) seedlings grown in Cd-contaminated solutions [ 94 ].…”
Section: Pbs For Phytoremediationmentioning
confidence: 99%
“…The uptake of PTEs increases with the addition of HA because HA contains several anionic functional groups namely hydroxyl (─OH) and carboxyl (─COOH), which can act as a ligand to complex with PTE ions. [ 57,58 ] These results demonstrate that soils with high contents of OM such as mangrove ecosystems, [ 59–61 ] tend to adsorb more PTEs.…”
Section: Resultsmentioning
confidence: 84%
“…[94][95][96] The highest percentage of the OM content at pH 5.5 was ≈30% which was detected in the subtropical mangrove ecosystem. [59][60][61] In this study, PTEs adsorption experiments were conducted by varying the OM content at 0%, 10%, and 30% with changes of PTEs concentrations ranging from 0 to 500 mg L −1 for six PTEs. In 100 mL conical flasks containing the specific concentration of a PTE, 1 g of finegrained soil (i.e., 0% OM), 0.9 g of fine-size soil and 0.1 g HA (i.e., 10% OM) or 0.7 g of fine size soil and 0.3 g HA (i.e., 30% OM) were added to each flask.…”
Section: Effects Of Soil Organic Matter Content On Adsorption Of Ptesmentioning
confidence: 99%
“…Cd complexation with chloride ion increases with salinity unit and different Cd species can be formed depending on the Cl − concentration: CdCl + , CdCl 2 0 , CdCl 3 − , CdCl 4 2− (Kubier et al, 2019). In organic‐rich waters, sorption of Cd by humic substances plays an important role in the speciation of Cd; the more humic substances, the less Cd in water (Pittarello et al, 2019).…”
Section: Sources Of Cadmium Contamination Plant Uptake Sequestration ...mentioning
confidence: 99%